EXPLORING THE RELATIONSHIP OF EMPATHY AND ASSURANCE ON ORGANIZATIONAL COMMITMENT AND MEDICAL PRACTITIONERS’ SATISFACTION: AN EMPIRICAL ANALYSIS OF JAWAHARLAL NEHRU MEDICAL COLLEGE - Bharadwaj, Yogendra Pal (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to explore the relationship of empathy and assurance on organizational commitment and their effect on medicinal practitioners’ satisfaction towards Jawaharlal Nehru Medical College (JNMC). It is an observational research where cross sectional design was used among 410 medical practitioners with the help of self administered questionnaire based on five point Likert scale. This study also used descriptive statistical technique and structural equation model to investigate their relationship. The results demonstrated that assurance is the primary determinant for medical practitioners’ satisfaction, trailed by organizational commitment. Nonetheless, assurance and empathy underscored inconceivably indicators for commitment and that eventually prompts medical practitioners’ fulfillment in JNMC.It will gigantically help both JNMC specialists and medical authorities in making reasonable frameworks to construct the tendency of medical practitioners’ satisfaction for a viable and effective organizational commitment through empathetic and assured course of action.This assessment is initiating as in the contemporary period medical experts’ fulfillment had tolerably been less researched in the Indian setting of JNMC and it is acting like a source that gives standard stuff to increase hierarchical commitment responsibility through empathy and assurance for the medical industry.